Analisis Pengembangan Karir Berbasis Kompetensi di UMKM Zainal Songket Palembang - Heriyanto Heriyanto; Dina Mellita; Andrian Noviardya; Efan Elpanso; Karmedi Santoso (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
This study examines that implementation of competency-based career development in Zainal Songket Palembang, a traditional creative industry that plays an important role in preserving local cultural heritage. Despite its long-standing existence and contribution to employment, career development practices remain informal and primarily based on experience and mentoring from senior workers. This study seeks to explain the process of competency development as well as identify obstacles encountered in the implementation process. Using a qualitative descriptive approach, data was collected through interviews observation, as well as documentary evidence as supporting data managers and employees from different divisions. The findings indicate that employees are given opportunities to improve their skills through hands-on practice, yet the absence of structured competency standards and formal training programs limits their career advancement. Additionally, the high workload and limited resources hinder the optimization of skill development. This  research emphasizes the importance of implementing a more structured approach.competency-based career framework to strengthen employee motivation, ensure regeneration of craftsmen, and support the sustainability and competitiveness of traditional creative industries such as Zainal Songket Palembang in the modern era.